Somatic growth in the first six months of life of infants exposed to maternal smoking in pregnancy - de Brito, Mariana Lopes (BMC Pediatr, 2017)
BACKGROUND: Some studies suggest a relationship between maternal smoking during pregnancy and not only intrauterine fetal growth restriction or low birth weight, but also with changes in the postnatal growth and development. The objective of the present study was to investigate the effects of smoking during pregnancy on infants growth in the first 6 months of life compared with a control group and a group with idiopathic intrauterine growth restriction. METHODS: Longitudinal observational study using a convenience sample of newborns divided into three groups: infants of smoking mothers (tobacco), with idiopathic intrauterine growth restriction (IUGR) and a control group. The sample was selected from two hospitals in Porto Alegre, located in southern Brazil, between 2011 and 2015. Newborns were evaluated at birth, 7 and 15 days, and in the first, third, and sixth month. Anthropometric measures were weight, length and head circumference. The growth indicators used were expressed as z-scores. The analyses were performed using the generalized estimating equation method. RESULTS: The sample included 273 mother/newborn pairs: 86 tobacco group, 34 IUGR group, and 153 control group. In terms of weight at birth, all groups differed significantly (p < 0.001). The birth length of tobacco and control groups were similar, but the IUGR group was lower than both (p < 0.001). We found no differences in growth trajectory between tobacco and control group, but there were differences in the growth of the IUGR group when compared with the other groups. At 6 months of age, all groups had similar anthropometric measurements. CONCLUSION: Intrauterine growth restriction had major impact on the growth trajectory of the infants studied, regardless of other factors, such as smoking and diet.